A triptycene-based enantiopure bis(diazadibenzoanthracene) by a chirality-assisted synthesis approach - Wang, Xubin; Kohl, Bernd; Rominger, Frank; Elbert, Sven; Mastalerz, Michael (Chemistry - a European journal, 2020)
By applying a chirality-assisted synthesis (CAS) approach enantiopure diaminodibromotriptycenes were converted to rigid chiral helical diazadibenzoanthracenes, which show besides pronounced Cotton effects in circular dichroism spectra higher photoluminescence quantum yields as comparable carbacyclic analogues. For the enantiopure building blocks, a protocol was developed allowing the large scale synthesis without the necessity of separation via HPLC.
First published: 10 July 2020
Gesehen am 28.10.2021